The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1590/0101-60830000000211
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation, reliability, and content validity of the Brief Negative Symptom Scale (BNSS) for use in Brazil

Abstract: Background: The Brief Negative Symptom Scale (BNSS) assesses the presence and intensity of negative symptoms in schizophrenia. Objectives: This study aimed to carry out the BNSS cross-cultural adaptation to the Brazilian Portuguese language and verify its content validity and reliability. Methods: This is a methodological study that followed these steps: (1) implementation of the cross-cultural adaptation and translation protocol, (2) BNSS adapted content validation, and (3) reliability assessment. Six experts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…While our Cronbach's alpha was 0.91, the Spanish study [13] found one of 0.98 and the Brazilian studies found 0.94 [11] and 0.88 [12]. Our sample size was surpassed by only one of these three studies that collected 111 patients [11], while the Spanish including 20 [13] and another Brazilian including 30 patients [12]. In sum, our findings confirm the cross-cultural properties of BNSS and extend previous validations in Brazilian Portuguese and Spanish cultures to European Portuguese.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…While our Cronbach's alpha was 0.91, the Spanish study [13] found one of 0.98 and the Brazilian studies found 0.94 [11] and 0.88 [12]. Our sample size was surpassed by only one of these three studies that collected 111 patients [11], while the Spanish including 20 [13] and another Brazilian including 30 patients [12]. In sum, our findings confirm the cross-cultural properties of BNSS and extend previous validations in Brazilian Portuguese and Spanish cultures to European Portuguese.…”
Section: Discussioncontrasting
confidence: 71%
“…When comparing our validation findings with the BNSS validation findings in samples closely related to European Portuguese, culturally and linguistically, such as the existing studies with a Spanish sample [13] and Brazilian patients [11,12], we found similar consistency metrics. While our Cronbach's alpha was 0.91, the Spanish study [13] found one of 0.98 and the Brazilian studies found 0.94 [11] and 0.88 [12]. Our sample size was surpassed by only one of these three studies that collected 111 patients [11], while the Spanish including 20 [13] and another Brazilian including 30 patients [12].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…BNSS was designed for easy application in the context of clinical trials or clinical routines and has excellent psychometric properties in schizophrenia [28,113] and in bipolar disorders (76). It has been translated and validated into 29 languages [141], notably Danish [142], Polish [143], German [144], Brazilian [68,145], and Spanish [146]. Nine translations were used in a European validation study [74].…”
Section: Second Generation Scalesmentioning
confidence: 99%